C−H Methylation of Iminoamido Heterocycles with Sulfur Ylides. (26th October 2020) - Ghosh, Prithwish; Kwon, Na Yeon; Kim, Saegun; Han, Sangil; Lee, Suk Hun; An, Won; Mishra, Neeraj Kumar; Han, Soo Bong; Kim, In Su
Abstract: The direct methylation of N ‐heterocycles is an important transformation for the advancement of pharmaceuticals, agrochemicals, functional materials, and other chemical entities. Herein, the unprecedented C(sp 2 )‐H methylation of iminoamido heterocycles as nucleoside base analogues is described. Notably, trimethylsulfoxonium salt was employed as a methylating agent under aqueous conditions. A wide substrate scope and excellent level of functional‐group tolerance were attained. Moreover, this method can be readily applied to the site‐selective methylation of azauracil nucleosides. The feasibility of gram‐scale reactions and various transformations of the products highlight the synthetic potential of the developed method. Combined deuterium‐labeling experiments aided the elucidation of a plausible reaction mechanism. Abstract : An unprecedented methylation of various iminoamido heterocycles by using Corey–Chaykovsky reagents is described. The use of aqueous solvent in the coupling reaction and the selective methylation and alkylation of azauracil nucleosides are highlighted.